Pengaruh Penggunaan Media Augmented Reality Assmblr Edu terhadap Hasil Belajar IPAS Siswa Kelas V - Musyarofah, Lailatul; Yulianto, Sigit (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the effect of Augmented Reality (AR) Assemblr EDU learning media on the science and social studies (IPAS) learning outcomes of fifth-grade students at Elementary School. A quantitative approach with quasi-experimental pretest-posttest control group design was employed. The research subjects consisted of 44 fifth-grade students, with 22 students in the experimental group and 22 students in the control group, selected through total sampling. Data were collected using cognitive test instruments that had been validated for reliability and validity. Data analysis included normality testing (Shapiro-Wilk), homogeneity testing (Levene), hypothesis testing (Independent Sample T-Test), and N-Gain analysis. Results showed that the experimental class average posttest score (93) was higher than the control class (79). The Independent Sample T-Test yielded t = 5.567 with significance <0.001, indicating a significant difference between both groups. The N-Gain value of the experimental class reached 70.35% (high category), while the control class obtained 40.22% (medium category). It is concluded that the use of AR Assemblr EDU media has a positive and significant effect on improving IPAS learning outcomes of fifth-grade students on the topic of Getting to Know Our Earth.